1986
DOI: 10.1099/0022-1317-67-5-831
|View full text |Cite
|
Sign up to set email alerts
|

Two Groups of Capsule-specific Coliphages Coding for RNA Polymerases with New Promoter Specificities

Abstract: SUMMARYFour bacteriophages (A 16, CK235, q~ 1.2 and K31) which specifically attack different encapsulated strains of Escherichia coli have been shown to be related to bacteriophage T7 (which is unable to grow on encapsulated hosts). The conclusion that phages A16 and CK235 are related to T7 is based on (i) similarities in the pattern of expression of intracellular phage proteins, (ii) early appearance, in infected host cells, of a phage DNA-specific RNA polymerase and (iii) hybridization (albeit to a low exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…BA14: the BA14-like phages include three isolates ( 29 , 30 ). Others: the RNAPs of the phages A16 and CK235 show substantial heterologous transcription on each other's DNA, but much lower activity on several other members of this group ( 32 ), so these two phages can be assigned to a separate subgroup. Similarly, the phages φ1.2 and K31 have even stronger heterologous transcription, and <10% activity on other members of this group, so they should also belong to a separate subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BA14: the BA14-like phages include three isolates ( 29 , 30 ). Others: the RNAPs of the phages A16 and CK235 show substantial heterologous transcription on each other's DNA, but much lower activity on several other members of this group ( 32 ), so these two phages can be assigned to a separate subgroup. Similarly, the phages φ1.2 and K31 have even stronger heterologous transcription, and <10% activity on other members of this group, so they should also belong to a separate subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The Vibrio parahaemolyticus phage VpV262 ( 24 ) and rosephage SIO1 ( 25 ) lack an RNAP gene in their genome, but contain a T7-like head structure module; thus, they have been thought to be members of the T7 supergroup ( 24 ). The Klebsiella phage K11 ( 26 , 27 ), Kluyveraphage Kvp1 ( 28 ), coliphage BA14 ( 29 , 30 ) and several others ( 3 , 31 , 32 ) were clearly shown to be closely related to phage T7, though no complete genome sequences are available for them.…”
Section: Introductionmentioning
confidence: 99%
“…Dietz et al also found two different promoter specificities associated with four capsule-specific coliphages. 66 These phages were not characterized by sequence analysis but two of them hybridized weakly to T7 DNA, and may thus be related to K1-5. It is not obvious how promoter specificities change, although a single amino acid change is sufficient to switch T7 RNAP from T7 to T3 promoter specificity.…”
Section: Evolution Of the Sp6 Groupmentioning
confidence: 98%
“…In Vibrio cholera, for example, phages that specifically lyse CPS + strains have been isolated and used to identify variants that lacked CPS (Albert et al, 1996). Specific phages infecting E. coli strains that possess CPS have also been isolated (Dietz et al, 1986;Clarke et al, 2000;Scholl et al, 2001). For other gram-negative bacteria such as Rhizobium meliloti, EPS have been demonstrated to inhibit phage adsorption by coating the cells (Defives et al, 1996).…”
Section: Bacteriophage Resistancementioning
confidence: 99%